Assessment of Misconceptions about Oral Health Care and Their Source of Information among Out-Patients Attending Dental College in Bangalore -A Cross Sectional Survey - Ajitha Kanduluru; S Manasa; D P Narayan; Mayurnath T Reddy; B K Sujatha (Wolters Kluwer Medknow Publications, 2013)
Background: Myths/misconceptions/false beliefs are the ideas/thoughts which are inculcated into human life during the course of lifetime. They are considered as an integral part of all the existing systems including healthcare. Aim: To assess the prevalence of misconceptions regarding oral health care and their source of information among out patients attending one of the dental colleges in Bangalore city. Materials and Method : A cross-sectional survey was conducted on a sample of 2021 out patients visiting Vydehi Institute of Dental Sciences and Research Centre, Bangalore using a self administered questionnaire. Data was collected and supervised by the investigator. Analysis was done using Chi square test and significance level was fixed at p< 0.05. Results: Out of2021 participants, 942 (46.6%) had poor level of knowledge; 431(21.3%) of them were found with average level of knowledge; 380(18.8%) of them had good level of knowledge, and 268(13.2%) of them had excellent level ofk:nowledge regarding oral health. Conclusions: Majority of the study population had considerable beliefs in myths and false perceptions regarding oral health issues. Most of them belonged to 36-45yrs age group, females, illiterates and unemployed.